Converging on Europe? The European Union in mediatised debates during the COVID-19 and Ukraine shocks - Christian Rauh; Michal Parizek (Journal of European Public Policy, 2024)
European integration is at risk of becoming stuck in a `politics' trap: Diverging national EU politicisation inhibits joint agreements which fuels public debates further. What can break this vicious circle? We argue that large and symmetrical exogenous shocks may reduce the divergence of national public EU debates to then study how the COVID-19 and Ukraine crises have altered mediatised EU portrayals across 753,435 articles from 228 major online news sites in the 27 EU member states during the 2018–2023 period. We find that the Covid and especially the Ukraine shock led to higher convergence in the public salience of the EU and the issue areas associated with this while partially also muting domestic party presence. However, we note that these effects appear short-lived. Large exogenous shocks thus do not lift the politicisation constraints on European integration permanently but offer at least windows of opportunity that may facilitate intergovernmental compromise.
https://doi.org/10.7910/DVN/SFFP0N
Keywords: 320; European integration; EU; politicisation; media; text analysis